The botanist's repository for new and rare plants; vol. 08 [of 10] - Andrews, Henry Cranke, active 1799-1828 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Botanist's Repository for New and Rare Plants; Vol. 08 [of 10]" by H. Andrews is a scientific publication written in the early 19th century. This volume continues a series dedicated to the detailed documentation of new and rare plant species, including color engravings alongside botanical descriptions in both Latin and English. The text serves as a valuable resource for botanists and horticulturists interested in the study and cultivation of exotic flora, particularly those introduced from various regions. The opening of this volume presents a series of detailed plates featuring individual plant species, each accompanied by thorough descriptions that outline their botanical classification, morphological features, and cultivation notes. For instance, the illustrations include the Bignonia Grandiflora and Scutellaria Serrata, describing their characteristics such as flower structure, leaf shape, and ideal growing conditions. The introduction of new species, their rarity, and the care necessary for their successful cultivation serve as a focal point in this botanical compendium, reflecting the author's dedication to advancing botanical knowledge and appreciation during a period of rich exploration in plant sciences. (This is an automatically generated summary.)
Release date is 2024-04-14
Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by Biodiversity Heritage Library.)
Keywords: Plants -- Pictorial works; Plants, Cultivated -- Pictorial works; Rare plants -- Pictorial works